Pengaruh pembelajaran Connected Mathematics Project (CMP) terhadap pemahaman konsep matematika pada siswa kelas VIII SMP Muhammadiyah Kuok - Alfarez, Ferdi; Wahyuni, Molli; Rizki, Lussy Midani; Bahasa Indonesia, Bahasa Indonesia (Jurnal PEKA (Pendidikan Matematika), 2025)
This research was motivated by the low mathematical reasoning abilities of class X students at SMAN 1 Salo. One solution to overcome this problem is to use problem-based learning. The aim of this research is to determine the differences in the mathematical reasoning abilities of students who apply problem-based learning and students who apply conventional learning. This research is an quasi experiment using a nonequivalent control group design. The research subjects consisted of class X-1, totaling 33 students and X-2, totaling 33 students. The sampling technique used was purposive sampling. The data collection techniques used were observation sheets and mathematical reasoning ability test questions. The results of this research can be concluded that there is a difference in the average test results of students' mathematical reasoning abilities in the experimental class using problem-based learning and the control class which applies conventional learning for class X students at SMAN 1 Salo. This can be proven through the Independent Sample T-Test, obtaining a sig(2-tailed) value of 0.023 < 0.05, so H0 is rejected and H1 is accepted.